2022
DOI: 10.1111/aas.14145
|View full text |Cite
|
Sign up to set email alerts
|

Markers of neutrophil mediated inflammation associate with disturbed continuous electroencephalogram after out of hospital cardiac arrest

Abstract: Background Achieving an acceptable neurological outcome in cardiac arrest survivors remains challenging. Ischemia‐reperfusion injury induces inflammation, which may cause secondary neurological damage. We studied the association of ICU admission levels of inflammatory biomarkers with disturbed 48‐hour continuous electroencephalogram (cEEG), and the association of the daily levels of these markers up to 72 h with poor 6‐month neurological outcome. Methods This is an observational, post hoc sub‐study of the COMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…31 The prognostic value of PCT after OHCA has been recently evaluated in a metaanalysis. 32 We found 14 individual studies on PCT, 3,[11][12][13]15,20,21,25,[33][34][35][36][37][38][39][40] including a total of 2608 patients. Nine studies reported an AUC value for the association between PCT concentration and poor outcome.…”
Section: Procalcitoninmentioning
confidence: 99%
See 4 more Smart Citations
“…31 The prognostic value of PCT after OHCA has been recently evaluated in a metaanalysis. 32 We found 14 individual studies on PCT, 3,[11][12][13]15,20,21,25,[33][34][35][36][37][38][39][40] including a total of 2608 patients. Nine studies reported an AUC value for the association between PCT concentration and poor outcome.…”
Section: Procalcitoninmentioning
confidence: 99%
“…11 Pekkarinen et al found no independent prognostic value of PCT when day two neurofilament light (NFL) was included in the multivariable model but a significant fixed effect for PCT was found for poor six-month neurological outcome. 39 Seven studies assessed PCT's prognostic value for neurological outcome or mortality after OHCA without adjusting for confounding variables. In a multicenter study of 932 patients, PCT on days one to three was significantly higher in patients with poor six-month neurological outcomes.…”
Section: Procalcitoninmentioning
confidence: 99%
See 3 more Smart Citations